Biomechanical Analysis of Cuboid Osteotomy Lateral Column Lengthening for Stage II B Adult-Acquired Flatfoot Deformity: A Cadaveric Study. Issue 3 (14th September 2018) - Yang, Yunfeng
Category: Midfoot/Forefoot Introduction/Purpose: To investigate the effect of cuboid osteotomy lateral column lengthening (LCL) for the correction of stage II B adultacquired flatfoot deformity in cadaver Methods: Six cadaver specimens were loaded to 350 N. Flatfoot models were established and each was evaluated radiographically and pedobarographically in the following conditions: (1) intact foot, (2) flatfoot, and (3) cuboid osteotomy LCL (2, 3, 4, and 5 mm). Results: Compared with the flatfoot model, the LCLs showed significant correction of talonavicular coverage on anteroposterior radiographs and talus-first metatarsal angle on both anteroposterior and lateral radiographs ( p < .05). Compared with the intact foot, the above angles of the LCLs showed no significant difference except the 2mmLCL. In terms of forefoot pressure, medial pressure of the 2mmLCL ( p = .044) and lateral pressure of the 3, 4, and 5mmLCLs showed statistical differences ( p < .05), but lateral pressure of the 3 mm LCL was not more than the intact foot as compared to the 4 and 5 mm LCLs, which was less than medial pressure. Conclusion: Cuboid osteotomy LCL procedure avoids damage to subtalar joint and has a good effect on correction of stage II B adult-acquired flatfoot deformity with a 3 mm lengthening in cadavers.